Kepraktisan E-Modul Matematika Berbasis Contextual Teaching and Learning Terhadap Kemampuan Pemecahan Masalah pada Materi SPLDV Kelas IX - Salafi, Lutfi Kurnia; Prihaswati, Martyana; Suprapto, Rohmat (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Technological developments have made significant contributions, technology has made substantial contributions across various sectors, including education. One example of its application in learning is the development of E-Modules as digital instructional media that can foster active student participation. This study aims to examine teacher and student responses and evaluate the implementation of a mathematics E-Module relying upon the Contextual Teaching and Learning strategy, merged with learning style assessments, concerning the materi of Linear Equation Systems with two variabel. An interpretative statistical mode was utilized within this investigation. Facts were compiled via reaction surveys, yang were additionally validated by conversations. The attendees comprised 32 kelas sembilan pupils and a single matematika guru at a sekolah in Kendal. The results showed yang the typical guru reaction mark reached 3.64, grouped as highly usable, whereas the typical student reaction mark hit 3.48, also grouped as highly usable. guru observed yang the materi shared inside the E-Modul was inclusive, orderly structured, and situational, thus successfully aiding the instructional cycle. Furthermore, learners mentioned yang the E-Modul offered a more fascinating educational encounter and satisfied their distinct learning style choices via its interactive display. Altogether, the created E-Modul was discovered to be fruitful in supporting pupils' awareness of the two variabel Linear Equation System idea and increasing their matematika pemecahan masalah talents, suggesting its possibility for wider usage. However, extra improvement is mandatory, specifically in facets of appearance, resource excellence, and the diversity of exercise masalah, to perfect the result.